Induced gonadal development and maturation of Japanese eel (Anguilla japonica) by injected 4-androstene-3,17-dione-cellulose acetate phthalate-microcapsule - DENG Yue-song; LIN Hao-ran; XU Zhi-rong (浙江大学学报. 农业与生命科学版)
The cellulose acetate phthalate-microcapsule which contained 4-androstene-3,17-dione was perpared. The testes of 75% Japanese eel, Anguilla japonica, were achieved maturation by injection 4-androstene-3,17-dione-cellulose acetate phthalate-microcapsule (ACM) three times at an interval of 25 d. The mean GSI of female eel were reached 33.54% by injection ACM four times at an interval of 25 d. The GtH contents in serum and pituitary were significantly increased both in male and female eel after inject sex steroid microcapsule.